Study on the transmissivity characteristics of urban trees in Szeged, Hungary - Takács, Ágnes; Kovács, Attila; Kiss, Márton (Hungarian Geographical Bulletin, 2016)
This study aims to determine the solar permeability characteristics of some common urban tree species in Hungary and to analyse their shading efficiency in mostly clear sky conditions. The results are based on ameasurement-series implemented during the whole vegetation period in 2015. This paper compares different tree species regarding their transmissivity, and looks for differences between different sized tree individuals belonging to the same species. The following order was found among the investigated species regarding their shading-capacity: T. cordata, A. hippocastanum and S. japonica. Additionally, higher transmitt ed radiation and consequently higher transmisivity values were detected in the case of the smaller investigated A. hippocastanum.